Mindfulness-Based Stress Reduction for lung cancer patients and their partners: Results of a mixed methods pilot study. (July 2015) - van den Hurk, Desiree G. M.; Schellekens, Melanie P. J.; Molema, Johan; Speckens, Anne E. M.; van der Drift, Miep A.
Background: Lung cancer patients and partners show high rates of impaired quality of life and heightened distress levels. Mindfulness-Based Stress Reduction has proven to be effective in reducing psychological distress in cancer patients. However, studies barely included lung cancer patients. Aim: We examined whether Mindfulness-Based Stress Reduction might be a feasible and effective intervention for patients with lung cancer and partners. Design: Mindfulness-Based Stress Reduction is a training in which mindfulness practices are combined with psycho-education to help participants cope with distress. In this mixed methods pilot study, questionnaires on psychological distress and quality of life were administered before, directly after and 3 months after the Mindfulness-Based Stress Reduction training, in combination with semi-structured interviews. Setting/participants: Patients with lung cancer and partners were recruited at one tertiary care academic medical centre. A total of 19 lung cancer patients and 16 partners participated in the Mindfulness-Based Stress Reduction training. Results: Most patients were diagnosed with advanced stage lung cancer. Vast majority completed the training. Those receiving anti-cancer treatment did not miss more sessions than patients who were not currently treated. Patients and partners felt positive about participating in a peer group and with their partner. Among participants no significant changes were found in psychological distress. Caregiver burden in partners decreased significantly after following Mindfulness-Based Stress Reduction. The qualitative analysis showed that the training seemed to instigate a process of change in participants. Conclusion: The Mindfulness-Based Stress Reduction training seemed to be feasible for patients with lung cancer and their partners. A randomized controlled trial is needed to examine the effectiveness of Mindfulness-Based Stress Reduction in reducing psychological distress in lung cancer patients and partners.